Physics of chromatic focusing, post-acceleration and bunching of laser-driven proton beams in helical coil targets. (3rd November 2020) - Bardon, M; Moreau, J G; Romagnani, L; Rousseaux, C; Ferri, M; Lefévre, F; Lantuéjoul, I; Etchessahar, B; Bazzoli, S; Farcage, D; Maskrot, H; Serres, F; et al.
Abstract: To increase the fluence and maximum energy of laser-driven proton beams in view of potential applications such as isochoric heating of dense material or isotope production, it has been proposed to attach a helical coil normally to the rear side of the irradiated target. By driving the target discharge current pulse through the coil, this scheme allows a fraction of the proton beam to be selected in energy and to be focused and further accelerated. The previously published results are extended to higher laser pulse energies and longer coils. This leads to an increased number of guided protons and the generation of several proton bunches. Large scale particle-in-cell simulations with realistic boundary conditions reproduce well the experimental results. A detailed analysis of the numerical simulations and an analytical model demonstrate that the current propagation along a helical wire differs from the one of a linear or folded wire. In a helical wire, the current pulse is subject to velocity dispersion, which results in progressive modification of its spatial profile, and so in proton bunch trapping and focusing.